The Effect of Business Mentoring, Digital Capability, and Quality Management Capacity on MSMEs’ Export Performance: The Mediating Role of Export Readiness - Intan Maria Lewiayu Vierke; Muhammad Aqib Shafiq (Bina Nusantara University, 2026)
This research examined the effects of business mentoring, digital capability, and quality management capacity on Micro, Small, and Medium Enterprises’ (MSMEs) export performance, with export readiness serving as a mediating variable. The research was conducted among MSMEs in DKI Jakarta. Using a quantitative explanatory design and Structural Equation Modeling - Partial Least Squares (SEM–PLS) analysis, data were collected from 100 export-oriented MSMEs through an online questionnaire. The results indicate that business mentoring, digital capability, and quality management capacity significantly enhance export readiness, and export readiness significantly improves export performance. However, export readiness does not significantly mediate the relationship between these three internal capabilities and export performance. The novelty of this research lies in its integration of business mentoring, digital capability, and quality management capacity within a single conceptual framework grounded in the Resource-Based View (RBV), Dynamic Capabilities Theory (DCT), and Export Readiness Theory (ERT), while empirically testing the mediating mechanism of export readiness in a metropolitan MSMEs context. The findings highlight that strengthening internal capabilities is essential to building export readiness. However, additional external factors are required to translate that readiness into measurable export performance.